(untitled) (Journal of Comparative & International Higher Education, 2021)
This paper investigates the impacts of recent, macro-level developments in transatlantic relations on the ability of United States and European Union higher education institutions (HEIs) to leverage international partnerships in achieving their traditional missions of teaching, research, and service. Using literature to place international education within the broader context of transatlantic relations from the post-World War II era to today, the connection between geopolitics and HEI international partnerships is made explicit. Comprehensive internationalization theory is then applied to illustrate the importance of HEI international partnerships in realizing international education outcomes that are congruent with traditional HEI missions. After establishing the link between transatlantic relations, internationalization in higher education, HEI international partnerships and overall HEI performance, recent developments within transatlantic relations are directly analyzed with regards to HEI international partnerships, highlighting impacts on their ability to function. Finding that progressive transatlantic relations result in improved performance outcomes through HEI international partnerships for US and EU HEIs, and that regressive transatlantic relations produce the opposite outcome, the study offers implications for policy makers and HEI administrators.